50-Hz magnetic field impairs the expression of iron-related genes in the in vitro SOD1G93A model of amyotrophic lateral sclerosis. (6th December 2018) - Consales, Claudia; Panatta, Martina; Butera, Alessio; Filomeni, Giuseppe; Merla, Caterina; Carrì, Maria Teresa; Marino, Carmela; Benassi, Barbara
Abstract: Purpose: We characterized the response to the extremely low frequency magnetic field (ELF-MF) in an in vitro model of familial Amyotrophic Lateral Sclerosis ( f ALS), carrying two mutant variants of the superoxide dismutase 1 (SOD1) gene. Materials and methods: SH-SY5Y human neuroblastoma cells, stably over-expressing the wild type, the G93A or the H46R mutant SOD1 cDNA, were exposed to either the ELF-MF (50 Hz, 1 mT) or the sham control field, up to 72 h. Analysis of (i) viability, proliferation and apoptosis, (ii) reactive oxygen species generation, and (iii) assessment of the iron metabolism, were carried out in all clones in response to the MF exposure. Results: We report that 50-Hz MF exposure induces: (i) no change in proliferation and viability; (ii) no modulation of the intracellular superoxide and H2 O2 levels; (iii) a significant deregulation in the expression of iron-related genes IRP1, MFRN1 and TfR1, this evidence being exclusive for the SOD1 G93A clone and associated with a slight ( p = .0512) difference in the total iron content. Conclusions: 50-Hz MF affects iron homeostasis in the in vitro SOD1 G93A ALS model.